The long wave of the Internet - Pietro Bonaccorsi; Massimo Moggi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
The Internet technology has radically transformed the computer and communication world, with revolutionary effects on economic and social systems at a global level. Its invention is the result of a collective research effort performed by computer scientists and telecommunications, electrical, software and computer engineers tied together in a sort of loosely coupled community, nurtured by US federal and military research programs. In this work we systematically recollect and reframe the contributions from the technological, business and economic history of the Internet into the interpretive framework provided by the evolutionary theories of technical change. More specifically, we show how the Internet as we know it is the outcome of the evolutionary processes followed by multiple technological innovations both in its transport infrastructure and in the applications grown out of it.
Keywords: O33; O31; 330; Internet history; Technological Paradigms; Technological Revolutions